Kedudukan Hukum Perseroan Terbatas Lembaga Keuangan Mikro Sebelum Diterbitkan Undang-Undang Cipta Kerja : Penelitian - Ambar Wihana; Endang Eko Wati; Rakhma Nurrozalina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to determine the legal status of Microfinance Limited Liability Companies (PT. LKM) established by Joint Village-Owned Enterprises (BUM Desa bersama) using revolving funds from the former National Program for Rural Community Empowerment (PNPM MPd) prior to the enactment of the Job Creation Law. The research method used was normative juridical with a legislative and conceptual approach. Based on the results of the research, it can be concluded that prior to the issuance of the Job Creation Law, the status of PT. LKM that used community revolving funds was not in accordance with the applicable laws and regulations, such as PT. LKM Kedungmas in Banyumas Regency. The results of this study are expected to provide input for PT LKM or other legal entities that manage revolving funds from PNPM MPd activities before the enactment of the Job Creation Law to comply with applicable laws and regulations.